(3QSGdI aj bjGe GdCQV aj hSW GdSeGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO aEf GdTjN CHj GdMSf CMeO Hf eMeO CeQfi Cf CTQM dg GdePgH GdMb s
(3BNQgG (B:s
(3GdLhGH dGf GdeGA YfO LehOg jfMUQ ai GLRGA ghGFjI JefYg ef GdQShH Edi CSad s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3hVYgG GHf SjfG ddTjN CHj GdMSf CMeO Hf eMeO GdSgjdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs